The Explosive Growth of U.S. Military Power on Guam Confronts People Power: Experience of an island people under Spanish, Japanese and American colonial rule - LisaLinda S. Natividad; Victoria-Lola Leon Guerrero (Asia-Pacific Journal, 2010)
The United States Department of Defense is planning a massive military build-up on Guahan (Guam) that threatens to change the entire make-up of the island. Guahan, nestled at the southern-most tip of the Marianas Archipelago in the Micronesian region of Oceania, is a mere 212 square miles in area, barely bigger than a dot in most world maps. The island is similarly small in the consciousness of most American and Japanese taxpayers, who will be funding the military expansion. Guahan, however, has a large and rich history. While the island and her people remained in relative isolation from the Western world for over 3,500 years from the earliest indications of settlement, its strategic location as a crossroad between East and West has resulted in colonization by successive maritime powers over the last six centuries.This article examines the plans for base expansion which threaten to swamp the local population, and the resistance to it, in light of Guahan's five hundred year colonial experience under Spain, Japan and the United States.